Reviews in Educational Psychology (Frontiers in Psychology 2010–2024): typology, topics, regional comparative and methodology toward digital and AI approaches - Alberto Díaz-Burgos; Jesús N. García-Sánchez; María-Lourdes Álvarez-Fernández; Sónia Brito-Costa; Sónia Brito-Costa; Douglas F. Kauffman; Ting-Chia Hsu; Jesús de la Fuente (Frontiers in Psychology, 2025)
This study presents a systematic review of reviews published in Frontiers in Psychology (2010–2024) to examine methodological and conceptual advances in educational psychology. The objective is to synthesize research trends over 14 years and explore global challenges, such as the digitalization of education and the integration of emerging technologies. Following PRISMA guidelines, a comprehensive search was conducted in Frontiers in Psychology, Web of Science, and Scopus, identifying 392 reviews. The selection process involved duplicate removal, title and abstract screening, and full-text evaluation, applying predefined inclusion and exclusion criteria to ensure methodological rigor. Data extraction and classification were carried out using an Excel-based structured database, analyzing publication years, methodological design, data sources, statistical and qualitative analysis methods, validation approaches, theoretical frameworks, thematic areas, geographical distribution, study limitations, reported results, practical applications and study populations. The methodological analysis highlights the predominance of systematic reviews, the increasing adoption of qualitative and mixed-method approaches, and a growing emphasis on digital tools and artificial intelligence. The study also reveals significant regional disparities in research output, with some regions being notably underrepresented. Beyond identifying trends, this review of reviews illustrates how psychology adapts to contemporary educational challenges through interdisciplinary methodologies and evidence-based strategies. The findings provide valuable insights into the evolving challenges in educational psychology, reinforcing the role of Frontiers in Psychology in driving methodological innovation and scholarly discourse. Furthermore, they contribute to the advancement of inclusive and sustainable educational practices aligned with the Sustainable Development Goals (SDGs). Future research should focus on meta-analyses of emerging trends, longitudinal methodological studies, and strategies to address regional imbalances, fostering a more globally representative perspective.